High‐Resolution Receiver Function Imaging Across the Cascadia Subduction Zone Using a Dense Nodal Array. Issue 22 (20th November 2018) - Ward, K. M.; Lin, F.; Schmandt, B.
Abstract: In the summer of 2017, we deployed 174 nodal geophones in the Cascadia Subduction Zone forearc with the specific aim of conducting a high‐resolution receiver function study. The dense trench perpendicular line in central Oregon with 500‐m spacing recorded continuous data for approximately 40 days. Our plate tectonic‐scale imaging results show the same features as previous broadband seismic deployments including the top of the subducting Juan de Fuca Plate, the slab Moho, and the continental Moho. Although our deployment was limited to around 40 days, the dense station spacing allowed us to image the shallow Oregon forearc in remarkable detail. In our shallow results, we image a continuous positive arrival that we interpret as the top of the accreted Siletzia terrane. We suggest that hybrid nodal/broadband deployments could be used in conjunction with offshore seismic studies to image subduction zones in unprecedented detail. Plain Language Summary: The largest earthquakes occur along subduction zones when energy stored along the plate interface is released during great subduction zone earthquakes. A component of understanding the hazards associated with such great earthquakes is knowledge of the subsurface Earth structure. For example, understanding the plate interface geometry in detail can improve predictions of how seismic waves propagate to the surface and help inform seismic hazard maps. In this study, we explore the use of a recently available seismometer technology that enables rapid deployment of large numbers of sensors with the aim of improving knowledge of Cascadia Subduction Zone structure in central Oregon. Our findings are presented in a proof‐of‐concept context where we demonstrate that the new seismometer technology is capable of resolving features seen in previous studies as well as new details owing to increased seismometer density. We suggest that this deployment scheme could be scaled and leveraged with offshore seismic experiments to explore the subsurface Earth structure along an active subduction zone in unprecedented detail. Key Points: We present results from the first large‐scale onshore three‐component nodal geophone deployment across a subduction zone forearc Radial receiver function images show the major subduction zone converters including the top‐of‐slab, slab Moho, and continental Moho High‐frequency receiver functions show strong continuous shallow crustal arrivals across the Siletzia terrane